Improving the specific strength of the arms and trunk according to plank exercises and the performance of shot put for young women - Abdul Mohsen , Zainab (Journal of Physical Education, 2025)
The modern qualitative idea of ​​training experienced athletes is not only strengths but also extends to general strength training, reaching special strength training in the training stages specific to the different types of sports activities. The aim of sports training is not to be on the relief of what prompted the researcher to practice the special strength of the arms and trunk and the achievement of the players pushing the weight. The study aimed to prepare plank exercises to improve the special strength of the arms and trunk and the achievement. I learned with moral success between the pre- and post-tests with the well-being of the Al Ain players pushing the weight for the youth players, numbering (5), then trying the exercise in the field and field in the scouts’ stadium. I got the (plank) exercises to a lot of positive and effective on the wonderful special strength and contributes to facilitating the arms and trunk and the achievement. The research experiment recommended the possibility of applying plank exercises in the special strength facilities for events in special athletics to learn more to achieve better.